A MODEL OF GROUP GUIDANCE TO ENHANCE STUDENT RESILIENCE IN THE COVID-19 ERA - Siti Aminah, Laila; Arifin, Wahyu Eko; Dja'far, Veri Hardinansyah (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2021)
This research aims to analyze group guidance model to enhance student resilience in the covid-19 era. This study employs a literature review is the method, by sifting through research publications published between 2015-2021. The majority of the publications were from national and international journals of guidance and counseling, psychology, and education. Using the keywords "Group Guidance," "Student resilience," and "Covid-19," which explored through journal article databases such ScienceDirect and Google Schoolar to compile the data. The findings demonstrates that teachers of guidance and counseling should assess their students' current degree of school involvement. Providing students with group counseling services is one way to get them more engaged in their education. As a result, teachers of Guidance and Counseling may consider offering group counseling sessions as a means of increasing student interest in school.